Eusirus bonnieri sp. nov. (Crustacea: Amphipoda: Eusiridae), a new deep species from the southeastern Bay of Biscay (NE Atlantic Ocean) - Othaitz, Junkal Peña; Sorbe, Jean Claude (Zootaxa, 2020)
A new bathyal eusirid, Eusirus bonnieri sp. nov., is described from the SE Bay of Biscay, mainly characterized by its strongly deflexed rostrum (not mentioned for any other known Eusirus species) and by a long spiniform process at the posterodistal corner of pereopods 5–7 merus. It was sampled with a suprabenthic sledge between 370 and 1099 m on southern margin of the Cap Ferret Canyon and within the Capbreton Canyon. It was relatively scarce on the open slope and its maximum abundance was registered within the upper part of the Capbreton canyon. Beside some ecological/biological data, an identification key is provided for all known species in this genus.